2010
DOI: 10.1002/14651858.cd003323.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Autologous chondrocyte implantation for full thickness articular cartilage defects of the knee

Abstract: Autologous chondrocyte implantation for full thickness articular cartilage defects of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
99
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(103 citation statements)
references
References 65 publications
0
99
0
4
Order By: Relevance
“…Previous studies have investigated tissue engineering and cellular therapies for treating early stage OA, and autologous chondrocyte implantation has demonstrated positive clinical outcomes (9,10). Nevertheless, due to the poor self-renewal and regeneration potential of chondrocytes, it is a slow process that may lead to fibrocartilage rather than hyaline cartilage (11,12). Furthermore, this two-stage surgical procedure and is predominantly used to treat cartilage defects caused by injury rather than OA.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated tissue engineering and cellular therapies for treating early stage OA, and autologous chondrocyte implantation has demonstrated positive clinical outcomes (9,10). Nevertheless, due to the poor self-renewal and regeneration potential of chondrocytes, it is a slow process that may lead to fibrocartilage rather than hyaline cartilage (11,12). Furthermore, this two-stage surgical procedure and is predominantly used to treat cartilage defects caused by injury rather than OA.…”
Section: Introductionmentioning
confidence: 99%
“…Не было зафиксировано статистически значимой разницы в функциональных результатах в двух исследованиях, сравнивающих АТХ с МФ. Оценка результатов шестого исследования, в котором сравнивались АТХ и МФ, была ограничена из-за большого числа выпадений из-под на-блюдения [82].…”
Section: ау тологичная трансплантация хондроцитовunclassified
“…A recent systematic review [Harris 2010] comparing these two techniques, looked at two other studies [Horas 2003 Despite the increasingly widespread use of autologous chondrocyte implantation, it remains unclear as to whether there is a significant difference between this and other cartilage repair techniques. A Cochrane Database Systematic Review [Vasiliadis 2010] concluded that there was insufficient evidence to draw conclusions on the use of autologous chondrocyte implantation in the knee.…”
Section: Autologous Chondrocyte Implantationmentioning
confidence: 99%